O projeto de incentivo da indústria bélica brasileira (2003-2013) - Ramos, Alexandre Arienti (2015)
This study deals with policies concerning Brazilian War Industries in the years 2003-2013, chaired by PT. In order to do so, it also analyzes Defense Policies in broad terms. Furthermore, we investigate the actions of the sector in order to promote its project through the participation of its intellectuals in forums and government committees. We also try to understand the organization of a certain discourse of the industrial sector in the press. In summary, we could observe that fractions of the War Industries have been successful in setting the agenda of policies for the sector, getting a number of benefits in tax, regulatory and protectionist terms. They also managed to make his project the majoritarian one for War Industries, regarding the format of private enterprises. In addition to analyzing the Political Defense, especially the ones focused on the War Industry, we performed a set of case studies of equipment purchasing programs by the Brazilian Armed Forces with the intent of understanding the real sense of the effective application of the policies listed. Through the contrast between political discourse and the real exercise of purchasing policies, we perceive a certain disharmony. If, on one hand, the discourse is based on nationalist arguments and promote autonomous development of technologies, the reality was marked by a process of denationalization of these sectors of the Brazilian War Industries through a subordinate integration to the international giants of War Industry